2017
DOI: 10.1093/mnras/stx1658
|View full text |Cite
|
Sign up to set email alerts
|

Earth-mass haloes and the emergence of NFW density profiles

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
81
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 56 publications
11
81
0
Order By: Relevance
“…Using an Einasto profile [65,66] instead amounts to a global increase ∼2 of the number of subhalos per flux decade within the considered integration regions ∆Ω. Please note that micro-halos with m M may show steeper inner slopes [67][68][69]; however, we have found that these micro-halos do not provide new bright, resolved subhalo candidates [1].…”
Section: Fixed Subhalo-related Quantitiesmentioning
confidence: 76%
“…Using an Einasto profile [65,66] instead amounts to a global increase ∼2 of the number of subhalos per flux decade within the considered integration regions ∆Ω. Please note that micro-halos with m M may show steeper inner slopes [67][68][69]; however, we have found that these micro-halos do not provide new bright, resolved subhalo candidates [1].…”
Section: Fixed Subhalo-related Quantitiesmentioning
confidence: 76%
“…The dependence of α and concentration parameter c = r vir /r s on the halo mass is given in I14. The cusp slope gradually becomes shallower with increasing halo mass through major merger processes (see also Ogiya et al 2016;Angulo et al 2017). The concentration parameter slightly depends on the halo mass.…”
Section: Subhalo Density Profilesmentioning
confidence: 98%
“…For masses below M * , haloes form efficiently following a power-law statistics, whereas for masses above M * , the number density falls of exponentially (Schechter 1976). In a scale-free Einstein-de Sitter universe, M * is the only driver of scale-dependence (Smith et al 2003;Angulo et al 2017), apart from the much smaller free-streaming scale (Angulo & White 2010), and hence the evolution of merger tree structures should be explainable by the evolution of M * (z). Explicitly, we expect the evolution of s to depend only upon the so-called peak amplitude ν ≡ δc/σ(M, z).…”
Section: Cosmic Evolution Of Tree Entropiesmentioning
confidence: 99%